The Meaning of National Insight in the Formation of Indonesian National Resilience - Pasha Rahima Swandari; Mifta Khoirul Anwar; Suparmi (Annujum: Journal of Humaniora and Law, 2025)
National resilience is a dynamic condition that reflects a nation's ability to maintain its survival and sovereignty amidst global challenges. This study aims to examine the role of national insight (wawasan kebangsaan) in forming Indonesia's national resilience through a literature study approach. The results show that national insight functions not only as an ideological concept but also as a moral, social, and cultural foundation that determines the nation's toughness. Social media, formal education, modern social dynamics, religious moderation, and the strengthening of social, economic, and ecological values have proven to play a role in strengthening national identity. The main challenges arise from globalization, digital disinformation, foreign cultural penetration, and weakening social solidarity among the younger generation. This study confirms that strengthening national insight must be carried out through an integrated strategy involving education, government, family, and the digital ecosystem. By managing adaptive and relevant national values, Indonesia's national resilience can be realized more firmly and sustainably.